2014
DOI: 10.1007/s10900-014-9897-8
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Healthcare Services Among Free Clinic Patients

Abstract: Free clinics provide free or reduced fee health services to the un- or under-insured. Patient engagement is important to understand patients' needs and to improve healthcare systems. There are few studies that examined patient engagement and satisfaction among the underserved and how patients perceive the quality of healthcare services in a free clinic setting. This study examined free clinic patients' satisfaction in order to better understand how free clinic patients perceive quality of healthcare services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
1
38
0
2
Order By: Relevance
“…In addition, there seems to be a direct relationship between mothers' satisfaction with the care received when these are compatible with the child's needs. A study has shown that mothers have greater satisfaction with the received care when they recognize that professionals are attentive to the work they do (14) . By interacting with professionals, family caregivers may feel satisfied with the care when they recognize that they (the professionals) have the knowledge about the work they do, meeting the needs of the children, promoting their welfare and recovery (15) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there seems to be a direct relationship between mothers' satisfaction with the care received when these are compatible with the child's needs. A study has shown that mothers have greater satisfaction with the received care when they recognize that professionals are attentive to the work they do (14) . By interacting with professionals, family caregivers may feel satisfied with the care when they recognize that they (the professionals) have the knowledge about the work they do, meeting the needs of the children, promoting their welfare and recovery (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Uninsured populations may therefore have little familiarity with continuity of care in terms of coordination and communication, a characteristic that previous research has identified as a significant indicator of patient satisfaction [8]. Previous studies have correlated patient satisfaction with free clinic resources such as interpreter services and health education services [9][10][11]. In general, patients are satisfied with services provided by free healthcare clinics, and participation in health education classes are found to be beneficial and contribute to patient satisfaction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have correlated patient satisfaction with free clinic resources such as interpreter services and health education services [9][10][11]. In general, patients are satisfied with services provided by free healthcare clinics, and participation in health education classes are found to be beneficial and contribute to patient satisfaction [9,10]. Existing research concludes that patients served by a free healthcare clinic are generally satisfied, but would experience higher satisfaction with the opportunity for increased awareness of programs and services that free clinics offer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Free clinic patients are highly satisfied overall with the healthcare services that they are able to access at a free clinic. [10][11][12] However, previous studies that used quantitative design failed to explain the depth of health-related challenges for this population. Nearly 80% of free clinics provide on-site health education, 5 although there is the possibility of missed opportunities for patient education in a free clinic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Language barriers in healthcare should also be investigated, given the gap between the number of patients who are not fluent in English and the number of those who actually used interpreter services. 11 Furthermore, both community resources and environment are essential to the health of free clinic patients and the underserved. Neighborhood environment is one of the primary predictors of health-related quality of life among free clinic patients.…”
Section: Introductionmentioning
confidence: 99%